2017
DOI: 10.1038/nsmb.3392
|View full text |Cite
|
Sign up to set email alerts
|

A cytosolic Ezh1 isoform modulates a PRC2–Ezh1 epigenetic adaptive response in postmitotic cells

Abstract: The evolution of chromatin-based epigenetic cell memory may be driven not only by the necessity for cells to stably maintain transcription programs, but also by the need to recognize signals and allow plastic responses to environmental stimuli. The mechanistic role of the epigenome in adult postmitotic tissues, however, remains largely unknown. In vertebrates, two variants of the Polycomb repressive complex (PRC2-Ezh2 and PRC2-Ezh1) control gene silencing via methylation of histone H3 on Lys27 (H3K27me). Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…It might also imply that CLF/SWN and FIE probably have distinct functions, although the clf swn double mutants share similar phenotypes with the fie mutants (Bouyer et al., ; Chanvivattana et al., ). In mammals, similarly, a partial overlap between the occupancy of H3K27 methyltransferases EZH1 and EED has been reported recently (Bodega et al., ).…”
Section: Resultssupporting
confidence: 58%
“…It might also imply that CLF/SWN and FIE probably have distinct functions, although the clf swn double mutants share similar phenotypes with the fie mutants (Bouyer et al., ; Chanvivattana et al., ). In mammals, similarly, a partial overlap between the occupancy of H3K27 methyltransferases EZH1 and EED has been reported recently (Bodega et al., ).…”
Section: Resultssupporting
confidence: 58%
“…Ezh1 remains the predominant, if not the exclusive H3K27‐HMTase expressed in differentiated tissues. In a recent study we reported that PRC2‐Ezh1 has a key repressive adaptive function specifically exerted in response to oxidative stress . We discovered a novel Ezh1 coding alternative splicing isoform expressed in healthy skeletal muscle fibers, lacking the catalytic SET domain, (Ezh1β).…”
Section: Novel Pcg Protein Isoforms: New Players In Epigenetic Contromentioning
confidence: 98%
“…Following ROS stress, phosphorylation by MAPK (mitogen activated protein kinase) negatively controls Bmi‐1 triggering its detachment from chromatin . Conversely, in skeletal muscle cells, oxidative stress induces increase of intra‐nuclear Eed level driving genome‐wide activation of PCR2‐Ezh1 complex and silencing of specific muscle gene networks . In Cardiac hypertrophy generated upon stress or hormone stimulation, the interaction between the lncRNA Chaer and PRC2, inhibits Ezh2 repressive function at hypertrophic genes leading to their induction …”
Section: How Do Polycomb Proteins Sense and Deal With Cellular Micro mentioning
confidence: 99%
See 2 more Smart Citations